The Roles of Macrophages in Heart Regeneration and Repair After Injury - Gao, Ying; Qian, Ningjing; Xu, Jingmiao; Wang, Yaping (Frontiers in Cardiovascular Medicine, 2021)
Although great advances have been made, the problem of irreversible myocardium loss due to the limited regeneration capacity of cardiomyocytes has not been fully solved. The morbidity and mortality of heart disease still remain high. There are many therapeutic strategies for treating heart disease, while low efficacy and high cost remain challenging. Abundant evidence has shown that both acute and chronic inflammations play a crucial role in heart regeneration and repair following injury. Macrophages, a primary component of inflammation, have attracted much attention in cardiac research in recent decades. The detailed mechanisms of the roles of macrophages in heart regeneration and repair are not completely understood, in part because of their complex subsets, various functions, and intercellular communications. The purpose of this review is to summarize the progress made in the understanding of macrophages, including recent reports on macrophage differentiation, polarization and function, and involvement in heart regeneration and repair. Also, we discuss progress in treatments, which may suggest directions for future research.